2019
DOI: 10.3390/cancers11101407
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Stress Response in HCV Infection Promotes STAT3-Mediated Inhibition of HNF4A-miR-122 Feedback Loop in Liver Fibrosis and Cancer Progression

Abstract: Hepatitis C virus (HCV) infection compromises the natural defense mechanisms of the liver leading to a progressive end stage disease such as cirrhosis and hepatocellular carcinoma (HCC). The hepatic stress response generated due to viral replication in the endoplasmic reticulum (ER) undergoes a stepwise transition from adaptive to pro-survival signaling to improve host cell survival and liver disease progression. The minute details of hepatic pro-survival unfolded protein response (UPR) signaling that contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…Therefore, hnf4a was determined to be a driver gene. It was reported that stress-induced inhibition of HNF4A expression is related to liver fibrosis and cancer formation [ 58 ]. Overexpressed Hnf5a resets the transcription factor network in hepatocytes and prevents hepatic failure [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, hnf4a was determined to be a driver gene. It was reported that stress-induced inhibition of HNF4A expression is related to liver fibrosis and cancer formation [ 58 ]. Overexpressed Hnf5a resets the transcription factor network in hepatocytes and prevents hepatic failure [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…MiR-122 was also found to play a role in the hypoxia responses that regulate glucose and energy metabolism (51). In addition, it was recently reported that ER stress impacts on miR-122 promoter activity (52). We found miR-638, miR−135a-5p, miR−135b-5p, miR-668-3p, miR-204-5p, miR−146a-5p, miR−200a-3p, miR−17-5p, miR−30a-5p, and miR−214-3p strongly correlated with lactate, base excess, and bicarbonate.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 activation was also explored in hepatocellular carcinoma (HCC) arising from hepatitis C infections. Aydin et al identified that HCC progression was mediated through NRF2, leading to STAT3 activation and suppression of miR-122 [ 36 ]. Finally, nano-formulated STAT3 inhibitors were also shown to be effective in myeloma xenograft models, enhancing the therapeutic properties of the inhibitor alone [ 37 ].…”
Section: Introductionmentioning
confidence: 99%